Spinal pseudomeningocoele: a diagnostic dilemma - Julia, P.E.; Nazirah, H. (2007)
Study design: Case report. Objective: To describe the difficulty in diagnosing spinal pseudomeningocoele. Setting: Department of Rehabilitation Medicine, University of Malaya Medical Centre, Kuala Lumpur, Malaysia. Case report: A case of progressive sacral swelling in a paraplegic man who sustained spinal cord injury 14 years ago is presented. Although his clinical features were suggestive of pseudomeningocoele, we were unable to confirm the diagnosis preoperatively. Conclusion: Traumatic spinal pseudomeningocoele is very rare. Even with the available modern diagnostic imaging techniques, it is still difficult to diagnose a spinal pseudomeningocoele.